A mathematical model for CO2 conversion of CH4-producing biocathodes in microbial electrosynthesis systems. (January 2022) - Li, Zhuo; Fu, Qian; Chen, Hao; Xiao, Shuai; Li, Jun; Liao, Qiang; Zhu, Xun
Abstract: Microbial electrosynthesis systems are a novel device for simultaneous CO2 reduction and CH4 production, and the CH4 -producing biocathode in this system is the key component. This work presents a mathematical model to insight into the process of CH4 production on the biocathode. The model couples bioelectrochemical reaction, charge balance, mass transfer, dissolution of gaseous CO2 and interconversion of hydrated CO2, H2 CO3, HCO3 − and CO3 2− . To our knowledge, this is the first theoretical report for CH4 -producing biocathodes in microbial electrosynthesis systems. This model is capable of predicting the response of CH4 -producing biocathodes with operating time under various conditions and describing the effects of different parameters on CH4 production. The results suggest that the most important processes which influence the performance of biocathodes are the interconversions of hydrated CO2, H2 CO3 and HCO3 − .